2015
DOI: 10.1021/jp511042x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous in Situ X-ray Absorption Spectroscopy and X-ray Diffraction Studies on Battery Materials: The Case of Fe0.5TiOPO4

Abstract: Following the reaction mechanisms of materials for Li-ion batteries under in situ conditions can provide vital new clues in the development of better battery materials. A new in situ cell was developed for such a purpose which allows an almost simultaneous measurement of XRD (X-ray diffraction) and XAS (X-ray absorption spectroscopy) at energies as low as the Ti K-edge. Change from one method to the other was possible in less than a minute at the Swiss–Norwegian Beamline (SNBL). Using this cell with its flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 15 publications
4
34
0
Order By: Relevance
“…According to the previous work on this family of materials like Ni 0.5 TiOPO 4 , Fe 0.5 TiOPO 4 and Cu 0.5 TiOPO 4 [18,23,28,29], the first large discharge capacity is related to the Ti 4 þ ions reduction to Ti 3 þ and Ti 2 þ , in parallel with the Co 2 þ reduction to Co°. In addition, the electrolyte decomposition occurring at low voltage and leading to the SEI layer (Solid Electrolyte Interface) formation is another source of the lithium uptake, as confirmed by our group for Ni 0.5 TiOPO 4 /C anode material [23].…”
Section: First Lithiation/delithiation Processesmentioning
confidence: 91%
“…According to the previous work on this family of materials like Ni 0.5 TiOPO 4 , Fe 0.5 TiOPO 4 and Cu 0.5 TiOPO 4 [18,23,28,29], the first large discharge capacity is related to the Ti 4 þ ions reduction to Ti 3 þ and Ti 2 þ , in parallel with the Co 2 þ reduction to Co°. In addition, the electrolyte decomposition occurring at low voltage and leading to the SEI layer (Solid Electrolyte Interface) formation is another source of the lithium uptake, as confirmed by our group for Ni 0.5 TiOPO 4 /C anode material [23].…”
Section: First Lithiation/delithiation Processesmentioning
confidence: 91%
“…1 On the other hand, Ti-based MB 0.5 TiOPO 4 (MB = Fe, Co, Ni, or Cu) materials have been researched and developed as high-capacity anode materials for lithium secondary batteries. [2][3][4][5][6][7][8][9] Y. Kee and coworkers reported the synthesis of rhombohedral LiTi 2 (PO 4 ) 3 and orthorhombic Li 1.5 Ti 2 (PO 4 ) 3 via the sol-gel method and the investigation of their use as anode materials for rechargeable Liion batteries. 10 S. Patoux and C. Masquelir reported that LiTiPO 5 / Super P carbon (SP carbon; MMM Carbon, Belgium) electrodes worked as active materials using cyclic voltammetry (CV) measurements and galvanostatic intermittent titration techniques (GITT).…”
Section: Introductionmentioning
confidence: 99%
“…The material turns amorphous quite rapidly with the reaction with the 1 st Na + per f.u. No intermediate phase of Fe0.5TiOPO4 is formed as demonstrated for Li-ion batteries [2]. The amorphisation is irreversible and during desodiation no further hint about the reaction mechanism can be found by in situ XRD.…”
Section: Resultsmentioning
confidence: 85%
“…Prior to in situ measurement, a careful analysis of structure of the synthetized powders (Fe0.5TiOPO4 and Cu0.5TiOPO4) can be found here [2,9]. A summary of those data is reported in the supplementary material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation